2017
DOI: 10.1016/j.egypro.2017.03.133
|View full text |Cite
|
Sign up to set email alerts
|

Flow Field and Performance Study of Vertical Axis Savonius Type SST Wind Turbine

Abstract: It has been suggested that waste heats or naturally available heat sources can be utilized to produce swirling flow by a design similar to that of split channels which is currently used to initiate fire whirls in laboratories. A new hybrid power system has been proposed combining the conventional Savonius wind turbine and split channel mechanisms. Previous computational and experimental works indicate a performance improvement in the new hybrid design (named as swirling Savonius turbine, SST) compared to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Blade for Performance Improvement rotated. The kinetic energy of the wind thus transforms into mechanical energy of rotation.The difference of drag force along the two sides of the rotor blades presents the main working principle of savonius wind turbine [6]. In recent years, various investigations have been carried out to develop Savonius rotor, by performing many modifications on the shape of blades, as well mounting extra components to the conventional rotor, to improve the performance, Table I shows different modified designs investigated.…”
Section: Modified Design Of Savonius Wind Turbinementioning
confidence: 99%
“…Blade for Performance Improvement rotated. The kinetic energy of the wind thus transforms into mechanical energy of rotation.The difference of drag force along the two sides of the rotor blades presents the main working principle of savonius wind turbine [6]. In recent years, various investigations have been carried out to develop Savonius rotor, by performing many modifications on the shape of blades, as well mounting extra components to the conventional rotor, to improve the performance, Table I shows different modified designs investigated.…”
Section: Modified Design Of Savonius Wind Turbinementioning
confidence: 99%
“…Although passive systems are easy to use and do not require active intervention, their effectiveness can be limited due to their static nature. In contrast, active control systems use complex electronics, sensors, and actuators to dynamically control the position of the blades [17]. This real-time adjustment capability allows blade rotation to be fine-tuned based on factors such as wind speed and generator load, resulting in increased efficiency and adaptation to changing wind conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Selecting an appropriate blade position control system for a wind turbine project requires a careful assessment of project requirements, costs, technical resources, and other relevant factors. Each system has its advantages and disadvantages, which makes the decision-making process important and complex [17]. However, the ultimate goal remains the same: to achieve the optimal position of the wind turbine blades for maximum efficiency and overall energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the wind potential with the consumption of electricity in the country suggests that wind turbines are able to generate 15 times more electricity than Kazakhstan needs [4]. The most promising area for the placement of wind turbines is the Shelek corridor, Dzhungar gates, Akmola region, Zhambyl region, according to studies conducted under the UN Development Program on wind energy [5]. Also, it was found that in Kazakhstan there are more than 50 thousand square kilometer areas with an average annual wind speed of 6 m/s or more.…”
Section: Introductionmentioning
confidence: 99%